To the Apple of God's Eye: Christian Zionist Travel to Israel - Shapiro, Faydra (Journal of contemporary religion, 2008)
This article examines a case of travel to Israel which might further complicate the already blurry line between tourism and pilgrimage: evangelical, Christian Zionist visits to Israel. The Israeli Ministry of Tourism estimates that evangelical Christians account for one third of American visitors to Israel. My research investigates how Christian Zionist travel to Israel is both touristic' and pilgrimage-like' and how this case can serve to question some thinking about pilgrimage. Finally, I offer yet another definition of what constitutes pilgrimage, which avoids at least some of the particular hazards. A primary goal of the research is to provide more empirical data and deeper analysis for our understanding of Christian Zionist travel to Israel and thus to contribute additional nuance to discussions of pilgrimage and tourism more generally.